2020
DOI: 10.1177/1753466620929231
|View full text |Cite
|
Sign up to set email alerts
|

Switching from omalizumab to mepolizumab: real-life experience from Southern Italy

Abstract: Background: Current availability of several biologic treatments for severe asthma makes it possible to choose the most appropriate for each patient. Sometimes a good percentage of patients with severe asthma may be eligible for biologics that target either the allergic phenotype or the eosinophilic one, but not all respond to that selected as first choice. The aim of our real-life study was to assess whether, for patients with severe eosinophilic allergic asthma, not previously controlled by the anti-IgE omali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 34 publications
3
28
0
3
Order By: Relevance
“…The most important finding of this study was not only the substantial improvement of asthma control, lung function, health status and the reduction of asthma exacerbations, but also the fact that switching between these two biologics without a wash‐out period did not resulted in any adverse events and/or tolerability issues, providing evidence that such an approach is feasible without significant safety concerns 49,50 . Similarly, one retrospective observational and one prospective real‐life study performed in patients poorly controlled with omalizumab who were seamlessly switched to mepolizumab provided similar results 51,52 …”
Section: How Should Switching Been Performedsupporting
confidence: 53%
See 1 more Smart Citation
“…The most important finding of this study was not only the substantial improvement of asthma control, lung function, health status and the reduction of asthma exacerbations, but also the fact that switching between these two biologics without a wash‐out period did not resulted in any adverse events and/or tolerability issues, providing evidence that such an approach is feasible without significant safety concerns 49,50 . Similarly, one retrospective observational and one prospective real‐life study performed in patients poorly controlled with omalizumab who were seamlessly switched to mepolizumab provided similar results 51,52 …”
Section: How Should Switching Been Performedsupporting
confidence: 53%
“…49,50 Similarly, one retrospective observational and one prospective real-life study performed in patients poorly controlled with omalizumab who were seamlessly switched to mepolizumab provided similar results. 51,52…”
Section: How S Hould Switching B Een Performedmentioning
confidence: 99%
“…224 Indeed, we have previously shown that around 40% of Omalizumab treated patients potentially qualify for Mepolizumab, had it been available at the time. 26 Furthermore, there have been emerging real-world data on biologic switching from anti-IgE to anti-eosinophil agents 225,226 in dual-eligible patients who did not respond to Omalizumab. This includes a real-world multicentre clinical trial (OSMO) 227 where switching has shown to not only be safe, but also efficacious in improving asthma control, healthcare utilization and exacerbations, even without an Omalizumab washout period.…”
Section: Omalizumabmentioning
confidence: 99%
“…26,[238][239][240][241][242][243][244][245][246][247][248] Their clinical efficacy was also observed in real-world patients who had failed Omalizumab therapy. 225,226,249,250 Real-world characterisation of patients receiving anti-IL-5/IL-5R drugs has identified a group who are older in age, have adult-onset asthma, predominantly male and have a high prevalence of nasal polyposis. 20,26 Nonetheless, not all patients respond well to these drugs, despite careful patient selection.…”
Section: Omalizumabmentioning
confidence: 99%
“…Indeed, some real-world data suggest that in clinical practice mepolizumab effectiveness can be even greater than that one observed in randomized controlled trials, and these better results might be dependent on the higher numbers of baseline blood eosinophils detectable in patients enrolled in reallife experiences (107,108). The latter have shown that mepolizumab is very effective in both non allergic and allergic patients with severe eosinophilic asthma, also in case of switching from omalizumab to mepolizumab because of an inadequate disease control provided by anti-IgE treatment (109)(110)(111). With regard to lung function, it is noteworthy that in real-life setting mepolizumab was able not only to increase FEV 1 , but also to improve airflow limitation at level of small airways (112).…”
Section: Licensed Biological Therapies Of Severe Asthmamentioning
confidence: 99%